Effect of Chemical Pretreatment of Sugarcane Bagasse on Biogas Production. (2020) - Kaur, Maninder; Neetu,; Pal Verma, Yajvender; Chauhan, Sanchita
Abstract: India produces about 352.16 MT of sugarcane annually. Although bagasse, the major byproduct of sugarcane crop is used by sugar industries itself for operating boilers but still around 3-5% of bagasse remains unutilized which often disposed off in open or burnt causing various health hazards and environmental pollution. Leftover bagasse still has huge amount of energy potential which can be further utilized in sustainable way to produce biogas. Using bagasse for biogas production and its by-products is a cost effective as well as eco-friendly step. In this study the comparison of effects of alkaline pretreatment of sugarcane bagasse on anaerobic co-digestion of bagasse with cow dung is investigated. The Bagasse is pretreated with 2%(w/v) solution of NaOH and 2%(w/v) solution of Ca(OH)2 at room temperature for one day. Alkali pretreated bagasse is then mixed with cow dung in ratio1: 2 and the solid to water is mixed in ratio 1: 3. Then the biogas production from the slurry formed is observed at 35°C and 55°C. Results showed that biogas production is highest from NaOH treated Bagasse followed by Ca(OH)2 treatment and without treated bagasse at 35°C. Further, it has been observed that biogas production at 55°C is higher than that at 35°C.